The effectiveness of psychometric measures in screening drug, alcohol and substance abuse - Othman, Mohamad Hashim; Isa, Abdul Majid; Hussin, Kamarudin; Abdull, Abdul Halim; Hussin, Huzili; Nazar, Mahmood; Kamarudin, Abdul Rani; Karim, Norazmah; Ku Aziz, Ku Azira (2014)
Urinalysis was used in previous studies among higher institution students (n=16252) in Malaysia to answer the question of whether university students are involved in drug abuse. However, the use of urinalysis had faced some problems. The problems were related to human rights issues and the cost to perform the urinalysis was expensive and quite impossible to be implemented to a large population of university students. To overcome this problem, this study was conducted to examine the effectiveness of psychometric measures in screening drug, alcohol and substance abuse. The Substance Abuse Subtle Screening Inventory A2 (SASSI-A2) was used for this purpose. SASSI-A2 is a brief screening tool designed to identify individuals who have a high probability of having a substance use disorder, including both substance abuse and substance dependence. SASSI-A2 comprises of 72 items that are rated on a two point scale with response; true and false. SASSI-A2 was translated into Malay language and it was refined through a back-translation technique and focus group approach. Psychometric testing was undertaken on a sample of 750 university students from five public universities in Malaysia. All participants were aged between 19 and 20 years. Internal consistency coefficients were calculated for the total scale and its subscales. Chronbach's alpha obtained for SASSI-A2 was 0.72. This relatively high level of Chronbach's alpha showed relatively high level of reliability. The results demonstrated that the whole SASSI-A2 meets the fundamental measurement properties and can discriminate groups of higher institution students from high to low on the substance dependency variable. The accuracy of the test has been found to be unaffected by gender, ethnicity, age and years of education. Although more rigorous validation studies are needed, it is recommended that SASSI-A2 be considered for usage to higher institution students populations when a brief, objective, and accurate screening tool for chemical dependency is needed.